233k views
0 votes
Consider the functions f(x) = 2x + 9 and g(x) = (x - 9)/2. Calculate the following.

A. g( f( 15)) B. g( f( -3)) C. g( f( x))

1 Answer

3 votes

9514 1404 393

Answer:

A. 15

B. -3

C. x

Explanation:

C. Since we want different values of g(f(x)), it is convenient to find that first.

g(f(x)) = g(2x +9) = ((2x +9) -9)/2 = 2x/2

g(f(x)) = x

__

A. g(f(15)) = 15

__

B. g(f(-3)) = -3

User SynergerySid
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.